2018
DOI: 10.1021/acschemneuro.8b00281
|View full text |Cite
|
Sign up to set email alerts
|

Identification of GSK-3 as a Potential Therapeutic Entry Point for Epilepsy

Abstract: In view of the clinical need for new anti-epileptic drugs (AEDs) with novel modes of action, we used a zebrafish seizure model to screen the anticonvulsant activity of medicinal plants used for traditional epilepsy treatment in the Congo, identifying 4 crude plant extracts that inhibited pentylenetetrazol (PTZ)-induced seizures in zebrafish larvae. Zebrafish bioassay-guided fractionation of an anticonvulsant Fabaceae species, Indigofera arrecta, identified indirubin, an bis-indole alkaloid with known inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 73 publications
0
49
0
Order By: Relevance
“…In this report, PTZ-treated zebrafish larvae were treated with both compounds, which exhibited anticonvulsant activity, with a reduction of epileptiform discharges. In the same way, indirubin and BIO-acetoxime showed anticonvulsant activity in the 6-Hz refractory seizure mouse model (Aourz et al, 2019).…”
Section: Therapeuticsmentioning
confidence: 61%
See 2 more Smart Citations
“…In this report, PTZ-treated zebrafish larvae were treated with both compounds, which exhibited anticonvulsant activity, with a reduction of epileptiform discharges. In the same way, indirubin and BIO-acetoxime showed anticonvulsant activity in the 6-Hz refractory seizure mouse model (Aourz et al, 2019).…”
Section: Therapeuticsmentioning
confidence: 61%
“…Memantine and ifendropil are NMDAR antagonists and have been demonstrated to conduct to GSK3β inactivation and reduction of tau phosphorylation (Liu et al, 2017). Recently, the use of potent and selective GSK3β inhibitors such as indirubin and BIO-acetoxime showed anticonvulsant properties (Aourz et al, 2019). In this report, PTZ-treated zebrafish larvae were treated with both compounds, which exhibited anticonvulsant activity, with a reduction of epileptiform discharges.…”
Section: Therapeuticsmentioning
confidence: 89%
See 1 more Smart Citation
“…In our study, the anticonvulsant potential of PTE was first evaluated in the zebrafish PTZ seizure test [ 10 , 13 , 21 ] and this assay demonstrated its evident seizure-suppressing activity. Interestingly, exposure time of 2 h was sufficient to detect its bioactivity, whereas most of the compounds required longer, usually 18 h, incubation to exhibit its properties.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, a group of authors from different countries have identified indirubin as the active principle responsible for the anticonvulsant properties of Indigofera arrecta (a traditional medicinal plant from Congo). Indirubin itself and 6‐bromoindirubin‐3‐acetoxime, both potent GSK‐3 inhibitors, are a new therapeutic entry point for epilepsy …”
Section: Introductionmentioning
confidence: 99%